PERANAN BIRO WANITA DAN SAYAP PEMUDA DALAM POLITIK PILIHAN RAYA SEMASA PILIHAN RAYA NEGERI SARAWAK 2021 DI TAMIN DAN MELUAN = THE ROLES OF THE WOMEN’S BUREAU AND YOUTH WING IN ELECTORAL POLITICS DURING THE 2021 SARAWAK STATE ELECTIONS IN TAMIN AND MELUAN - Lucy, Sebli-Seidelson; Awang Mashabi, Awang Mohamad; Haslina, Hashim (Penerbit Universiti Sains Malaysia, 2024)
This article examines the electoral politics of the 2021 Sarawak State Election (SSE21), focusing on the Women’s Bureau and Youth Wing of Parti Rakyat Sarawak (PRS) and the Progressive Democratic Party (PDP). Using the framework of clientelism, the study investigates the interdependent relationships between the women’s bureau, youth wing and candidates. From the outset, it is evident that the provision of rewards and services by candidates both before and after the election played a significant role in consolidating the support of the women’s bureau and youth wing members, particularly towards the incumbent candidates. The research was conducted through observations and in-depth interviews with candidates, PRS and PDP representatives, women’s bureau and youth wing members, youth leaders, and community leaders, including tuai rumah and penghulu, in the State Legislative Assembly (SLA) of Meluan and Tamin.